2021
DOI: 10.1016/j.xcrm.2021.100329
|View full text |Cite
|
Sign up to set email alerts
|

Serological analysis reveals an imbalanced IgG subclass composition associated with COVID-19 disease severity

Abstract: COVID-19 is associated with a wide spectrum of disease presentation, ranging from asymptomatic infection to acute respiratory distress syndrome (ARDS). Paradoxically, a direct relationship has been suggested between COVID-19 disease severity and the levels of circulating SARS-CoV-2-specific antibodies, including virus neutralizing titers. A serological analysis of 536 convalescent healthcare workers reveal that SARS-CoV-2-specific and virus-neutralizing antibody levels are elevated in individuals that experien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
80
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 40 publications
12
80
3
1
Order By: Relevance
“…They may be related to the temporal model of affinity maturation, with the IgG3 response earlier, with a switch to a higher affinity IgG1 antibody response later [ 26 ]. Also, it has been reported that the time-point of donation as well as disease severity are factors influencing the outcome of the antibody profile [ 27 ]. Alternatively, the variations could be due to methodological differences in how the neutralization assays were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…They may be related to the temporal model of affinity maturation, with the IgG3 response earlier, with a switch to a higher affinity IgG1 antibody response later [ 26 ]. Also, it has been reported that the time-point of donation as well as disease severity are factors influencing the outcome of the antibody profile [ 27 ]. Alternatively, the variations could be due to methodological differences in how the neutralization assays were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…We similarly documented elevation in RBD-specific IgG1 and IgG3 levels in the serum of all mothers after the second vaccine dose. Recent studies have described the dominance of IgG1 and IgG3 response over IgG2 and IgG4 following SARS-CoV-2 mRNA vaccination and with natural infection (24)(25)(26). The lower IgM levels after the second vaccine dose may be related to enhanced class switching to IgG and IgA isotypes after this dose.…”
Section: Discussionmentioning
confidence: 99%
“…More surprising was that, when detected, the MALDI-ToF mass spectra of total IgG3Hc was also significantly higher in the COVID-19 ARDS convalescent plasma (see figure 2). It had been reported that a dominance of anti-SARS-CoV2 IgG3 occurs in the immune responses to SARS-CoV2 in those who died from COVID-19 [14]. We had shown an increase in the mass of IgG3Hc bound to SARS-CoV2 prefusion Spike protein and eluted from magnetic bead to which it was conjugated [13].…”
Section: Discussionmentioning
confidence: 62%
“…infection [14]. The possibility is that elevated glycated albumin along with elevated levels of IgG3 characterised by an increased molecular mass (due to glycation/glycosylation) may act as biomarkers of susceptibility to develop ARDS as a result of SARS-CoV2 infection.…”
Section: Introductionmentioning
confidence: 99%